2010
DOI: 10.1007/s00520-010-0879-9
|View full text |Cite
|
Sign up to set email alerts
|

Music’s relevance for pediatric cancer patients: a constructivist and mosaic research approach

Abstract: Health professionals should consider ways to assist parents who are often using music to support children with cancer. Hospitals can promote pediatric cancer patients' resilience by providing music-based support services, including music therapy, and reducing unwanted stressful sounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 29 publications
(50 reference statements)
2
60
0
1
Order By: Relevance
“…The study recommended that health professionals help parents through the use of music and that hospitals can reduce the resistance of pediatric cancer treatment and the hospitalization process, providing support services based on the use of music. 15 Similar results were found in another study, developed by Australian researchers, who evaluated the clinical practice of music therapy services in pediatric oncology hospitals. The participants were children and adolescents between zero and 16 years and parents of children who did not have conditions to respond to the questionnaire.…”
Section: Use Of Music In the Care Of Children And Adolescents With Casupporting
confidence: 81%
See 1 more Smart Citation
“…The study recommended that health professionals help parents through the use of music and that hospitals can reduce the resistance of pediatric cancer treatment and the hospitalization process, providing support services based on the use of music. 15 Similar results were found in another study, developed by Australian researchers, who evaluated the clinical practice of music therapy services in pediatric oncology hospitals. The participants were children and adolescents between zero and 16 years and parents of children who did not have conditions to respond to the questionnaire.…”
Section: Use Of Music In the Care Of Children And Adolescents With Casupporting
confidence: 81%
“…Access to your favorite music activates creativity, fun and laughter, whose value is incalculable, especially when cancer becomes a limiting life factor. [15][16] …”
Section: Discussionmentioning
confidence: 99%
“…Parents also have a unique vantage point as key informants for evaluating behavioral interventions. Parental perspectives on music therapy interventions for children/adolescents with cancer offer a perspective on the benefit of such interventions, while also providing insight into the value of an intervention for themselves [10-13]. This paper presents a study of parental perspectives on the helpfulness and meaningfulness of a behavioral music therapy intervention targeted to AYA undergoing transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Music experienced by children with cancer can facilitate resilience and "normality" [32]. The authors often observed music used by AYA at Peter MacCallum Cancer Centre and decided to examine music's relevance for this group.…”
Section: Music In Adolescent and Young Adult Livesmentioning
confidence: 99%